Analisis Dinamika Psikologis Eksistensial Tokoh Utama pada Novel Bandung Menjelang Pagi Karya Brian Khrisna: Kajian Psikologi Eksistensial Rollo May - Nurul Setyorini; Annisatun Azizah Maahayyu Dianti; Dwi Noviyanti; Nabila Mayang Siwi; Arifah Tri Solecha (Pusat Riset dan Inovasi Nasional, 2024)
One of the uniqueness of this novel is its content which is rich in psychological problems that occur in people’s lives and is quite a big concern. The purpose of this study is to represent the psychological existence of the main character in the novel Bandung Menjelang Pagi by Brian Khrisna in the form of anxiety, guilt, intentionality, care, love, and desire, freedom and destiny, the power of myth, psychopathology, and psychotherapy, reviewed using an existential psychology approach. The data source for this study is the novel Bandung Menjelang Pagi by Brian Khrisna. This study uses a qualitative descriptive method carried out using the technique of listening and taking notes. The research instrument used is a human instrument, making oneself (the author) the instrument. The data analysis technique used is the content analysis technique. The results of the research that has been conducted are that there are 129 psychological existence data of the main character in the form of anxiety consisting of 6 (4.7%) normal anxiety data and 4 (3.1%) neurotic anxiety data, forms of guilt consisting of 1 (0.8%) unwelt data, 6 (4.7%) mitwelt data, and 5 (3.9%) eignwelt data, forms of intentionality consisting of 12 (9.3%) data, forms of caring consisting of 7 (5.4%) data, forms of love consisting of 2 (1.6%) sex data, 11 (8.5%) eros data, 3 (2.3%) philia data, and 9 (7.0%) agape data, and 13 (10.1%) desire data, forms of freedom consisting of 9 (7.0%) existential data and 3 (2.3%) essential data, and 8 (6.2%) destiny data, 5 (3.9%) data on the form of mythical power, 15 (11.5%) data on the form of psychopathology, and 10 (7.7%) data on the form of psychotherapy.